Systematic Literature Review: Pengembangan Media Video Animasi pada Pembelajaran IPA di Sekolah - Hidayat, Abib; Azhar, Aulia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Animated videos have proven to be effective as learning media to reduce learning difficulties, especially in science subjects. The purpose of this study was to determine how the development of animated video media is applied in science learning in schools. The study was conducted using the Systematic Literature Review (SLR) method on articles published between 2021 and 2024. The results of the study of three Research Questions (RQ) showed that the limited use of animated videos in science learning has encouraged many researchers to develop this media. The most frequently used development model is ADDIE, because it is considered systematic and easy to apply. Meanwhile, Powtoon software is the main choice because it is practical and capable of producing attractive animations. This study is expected to be a reference for educators in designing animated video media that can help students understand science concepts more easily and enjoyably.